The Impact of Islamic Jurisprudence Principles on the Urban Planning of Historic Cities - Ourkia, Abderrazak; Alsaied, Mohamad Abdullah (Journal of Posthumanism, 2025)
Architecture constituted the most tangible signature of medieval Islamic civilisation, yet its forms were never left to personal whim or isolated royal decrees. Instead, a dense corpus of juristic writing—especially Mālikī treatises on construction (bunyān) and easements (irtifāq)—functioned as a de facto planning code guiding historic Muslim cities. Analysing three foundational manuals (Ibn ʿAbd al Ḥakam, 271 AH; ʿĪsā al Tuṭīlī, 386 AH; Ibn al Rāmī, 8th c. AH) alongside fatwā collections and nawāzil, the article reconstructs a coherent set of urban regulations embedded in classical fiqh. It demonstrates how the maxim “no harm and no reciprocal harm” and allied principles of public interest, lesser harm choice, and custom shaped city form, from street hierarchies to industrial zoning. The study shows that juristic rulings mandated load bearing limits, demolition of unsafe walls, minimum road widths, and height clearances for balconies; outlawed dumping debris and discharging wastewater into streets; located smoke emitting crafts outside residential quarters; protected courtyards, gardens, and riverbanks; and prescribed privacy features such as inward oriented houses and high, narrow windows. These regulations reveal fiqh as a dynamic instrument of urban sustainability rather than a static legal relic. By correlating textual rulings with archaeological maps of Medina, Fez, and Marrakesh, the paper evidences their materialisation in street dimensions, courtyard proportions, and craft districts. The findings invite contemporary planners and heritage professionals to mine fiqh archives for locally resonant sustainability guidelines that complement international charters. It positions Islamic jurisprudence as a resource for global urban history and culturally rooted regeneration of historic fabrics. Five findings emerge: overarching legal maxims, structural safety codes, public health prescriptions, environmental zoning, and privacy/sanctuary rules. Methodologically, the article unites close readings of Mālikī texts with morphological evidence from Medina, Fez and Marrakesh, showing how written rulings translated into street widths, garden buffers and industrial quarters, yielding insights for heritage tourism and context sensitive planning.